Robust datamining - Uwe, Aickelin (2017)
Our long-term research goal is to develop datamining methodologies that are robust to changes in data and uncertainty. By robust we mean solutions remain ‘optimal’ when things change or are easily repaired. Broadly, this robustness can be achieved in two ways: One, by having ‘slack’ in the solution or two, by constructing the solution such that is easily repairable, e.g. failures are isolated.